Mineral composition of torula yeast (Candida utilis), grown on distiller?s vinasse - Rodr?guez, B?rbara; Canela, A. A.; Mora, Luis Marino; Motta, W. F.; Lezcano, Pedro; Euler, Ana Carolina (Cuban Journal of Agricultural Science, 2011)
A neutron activation analysis was conducted to determine the minerals in torula yeast grown on distiller?s vinasse. The mineral material and total phosphorous were determined according to AOAC (1995). The presence of 23 elements of the periodic table was determined in the analysis by neutron activation. Potassium (K), calcium (Ca), chloride (Cl), manganese (Mg), iron (Fe) and sodium (Na) were those of largest concentration. It was proved that there was high content of mineral material (7.15 %) and total phosphorous (1.61%) in the yeast. The mineral composition of the torula yeast from vinasse showed higher values for Ca, K, Fe and Zn than those reported by the NRC (1998) in soybean meal and torula yeast. Key words: yeast, minerals, neutron activation.